1995
DOI: 10.1002/ajmg.1320570405
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variability of clinical manifestations in Waardenburg syndrome

Abstract: Expression of clinical findings of Waardenburg syndrome type 1 (WS1) and type 2 (WS2) is extremely variable. Using our collection of 26 WS1 and 8 WS2 families, we analyzed the occurrence, severity, and symmetry of clinical manifestations associated with WS. We found significant differences between WS1 and WS2 in deafness, and in pigmentary and craniofacial anomalies. Factor analysis was used to identify manifestations which covaried, resulting in 2 orthogonal factors. Since mean factor scores were found to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
4
15
0
3
Order By: Relevance
“…Arias and Silan claimed that type 2 was more common than type 1 [Arias, 1971;Silan et al, 2006], while the majority of reports presented more cases of WS1 [Pardono et al, 2003]. In the present study, the distribution of our patients was in agreement with Arias' and Silan' studies, since we also found more type 2 cases (62.1% WS2 vs. 37.9% WS1) than others where the frequency of type 1 was higher [Reed et al, 1967;Liu et al, 1995;Reynolds et al, 1995]. This difference may be due to ascertainment bias, since we were looking for WS patients among educational centers for the deaf children and deafness is known to be more common in WS2.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Arias and Silan claimed that type 2 was more common than type 1 [Arias, 1971;Silan et al, 2006], while the majority of reports presented more cases of WS1 [Pardono et al, 2003]. In the present study, the distribution of our patients was in agreement with Arias' and Silan' studies, since we also found more type 2 cases (62.1% WS2 vs. 37.9% WS1) than others where the frequency of type 1 was higher [Reed et al, 1967;Liu et al, 1995;Reynolds et al, 1995]. This difference may be due to ascertainment bias, since we were looking for WS patients among educational centers for the deaf children and deafness is known to be more common in WS2.…”
Section: Discussionsupporting
confidence: 94%
“…Since the phenotypic expression of the syndrome is extremely variable, clinical diagnostic criteria have been established by an international WS consortium [Liu et al, 1995;Reynolds et al, 1995], which includes major and minor clinical manifestations [Arias, 1971;McKusick, 1994;Liu et al, 1995;Reynolds et al, 1995;Pardono et al, 2003]. …”
Section: Introductionmentioning
confidence: 99%
“…Allelic heterogeneity at PAX3 may also influence clinical features, just as mutations are now known at the cystic fibrosis locus which lead to congenital absence of the vas deferens with out any other features of cystic fibrosis [36], Identification of additional WS genes will lead to a better understanding of the clinical variability which characterizes this disorder. Associated studies from our laboratory have found differences in the occurrence, severity, and laterality of some of the common clinical symptoms among WS1 PAX3-linked and WS2-affected individuals [37], A finding of that study which is particularly relevant to the present report is the variability in the expres sion of dystopia among affected individuals in PAX3-linked families. These data, as well as data for other families [38], show that some clearly affected members of type 1 families do not exhibit dystopia canthorum (as measured by the W-index).…”
Section: Discussionsupporting
confidence: 55%
“…Obwohl eine hohe Penetranz angegeben wird, sind die klinischen Charakteristika bei den betroffenen Individuen sogar innerhalb einer Familie sehr unterschiedlich [3,8,12,14]. So auch in unserer Familie: wĂ€hrend bei der Mutter (H-9) lediglich der fundoskopische Befund auffĂ€llig war (fleckige Hyper-und Depigmentierungen der Peripherie), waren bei den zwei betroffenen Söhnen (11I-4, I11-5) ausgeprĂ€gte Pigmentstörungen der Augen und schwere Hörstörun-gen vorhanden.…”
Section: Diskussionunclassified
“…Bei WS Typ 2 betroffenen Individuen wurde eine besonders hohe Inzidenz von Taubheit, zumeist beidseitig auftretend, festgestellt [8,14,15,24]. Auch diese Hörstörung kann erklĂ€rt werden durch ein lokales, umschriebenes Fehlen der Melanozyten in der Stria vascularis der Cochlea [13].…”
Section: Diskussionunclassified